Enhancing Tofu Wastewater Treatment Efficiency with Water Hyacinth Extract Addition in an Anaerobic Sequencing Batch Reactor - Laily Isna Ramadhani; Salma Ainun Nabila; Santa Angela; Herawati Budiastuti (Fluida, 2025)
Tofu production results in wastewater containing high levels of organic matter. This wastewater needs to be treated before discharging into water bodies. Anaerobic wastewater treatment is capable to decompose organic compounds in wastewater and can produce biogas. Tofu wastewater has a low C/N ratio (6.51), so it needs to be increased by adding water hyacinth extract. The reactor used is an Anaerobic Sequencing Batch Reactor (ASBR) with cow rumen extract as a starter at a concentration of 7,995 mg MLVSS/L. The concentration of tofu wastewater used was 6,000 mgCOD/L, and water hyacinth extract was added at a concentration ratio of 15:2. This research aims to determine the reduction in COD and cumulative biogas volume gain during tofu wastewater treatment with the addition of water hyacinth extract. The parameters tested in the research were MLVSS, COD, pH, and cumulative biogas volume. The efficiency of reducing COD concentration at the operational stage with adding water hyacinth extract was 87.5%, while the reduction in COD concentration without adding water hyacinth extract was only 56.25%. The cumulative volume of biogas produced for 9 days of operation was 7,300 mL, while the ASBR operation without adding water hyacinth extract was 9,590 mL for 9 days.